Respuestas
Respuesta dada por:
0
Explicación paso a paso:
9x²+x-18x-2=0
x×(9x+1)-2(9x-1)=0
(9x+1)×(x-2)=0
9x+1=0
x-2=0
x= -1/9
x=2
bueno una de esas es tu respuesta creo bueno se incluye las imagenes
Adjuntos:
![](https://es-static.z-dn.net/files/d16/d061196eba2a563a9d34bbd17ec93e71.jpg)
![](https://es-static.z-dn.net/files/df5/b5dffcedc01095c0e5afc6e7daee83f7.jpg)
![](https://es-static.z-dn.net/files/dce/85fc964bc830ee04cf1daae9b1746c36.jpg)
![](https://es-static.z-dn.net/files/d5b/4675048e89da8b165c34f51ca904fb5e.jpg)
![](https://es-static.z-dn.net/files/da6/396a04c9b85c76b6d7cd83dc84352d0b.jpg)
Preguntas similares
hace 5 años
hace 5 años
hace 5 años
hace 8 años
hace 8 años
hace 8 años
hace 9 años